Використання imagebutton, як спосіб інтерактивності в візуальних новелах - Котляревська, Ю. А.; Ганич, О. К.; Клішина, М. С. (ХНУРЕ, 2025)
This work is devoted to the use of image button as a means of interactivity in visual novels developed with the Ren'Py engine. The main features of the image button function, its properties, and applications for enhancing player interaction with the game world are considered. A comparison with imagemaps has been conducted, highlighting the advantages of image-based buttons in creating a dynamic and intuitive interface. Examples of image button usage for interactive choices, environmental exploration, and storyline impact are provided.
Keywords: imagebutton; Ren'Py engine